Phycodegradation of polyethylene by photosynthetic microalgae - Prakash Murgeppa, Bhuyar (2020)
Plastic pollution has become one of the most reported environmental issues, as rapidly increasing production of disposable plastic products overwhelms the world’s ability to deal with them. Malaysia is the eighth largest country to generate plastic waste in the list of developing countries. Conventional methods of polyethylene degradation including incineration, landfill, and chemical treatment are lethal to the neighboring environment and causing hazardous effects on living organisms. There is no efficient, economical, and green solution for the complete degradation of polyethylene formulated at both academia and industrial scale. However, to solve this global issue, biological mode could possibly be evaluated and developed in the upcoming future. In this research investigation, the potential of consortium green algae (Chlorella sp.) and blue-green algae (Cyanobacteria sp.) was investigated for biodegradation of low-density and high-density polyethylene. The objectives of this research were to study the physio-chemical structure of low- and high-density polyethylene and to identify the potential microalgae for the biodegradation of both polyethylene followed and to study analytical characterization of treated polyethylene. Finally, the biodegradative compounds has been analyzed. Results obtained showed that fluorescent and scanning electron microscopic observation of polyethylene sheet has shown the colonization of microalgae with exopolysaccharides on the polyethylene film which initiates the corrosion of polymer surface. The weight loss results reveled that consortium traded low-density polyethylene weight reduced was observed about 8.18% ± 0.66 and the high-density polyethylene about 6.43% ± 0.59. Energy dispersive x ray analysis revealed the after the consortium treatment carbon content decreased to 53.18 % for low- density and 31.15 % for high density polyethylene. The CHNO analysis shown 37.91% and 41.74% of carbon content reduction for low- and high-density polyethylene film respectively after degradation. Thermal analysis results displayed efficient reduction in melting of treated polyethylene compared with control. Fourier infrared spectrum evident that both the polyethylene’s are degrading with prominent decrease in transmittance of C-H bond and increase in OH and C-O bond signal. Finally, exopolysaccharide analysis showed the microalgae consortium exhibited the larger quantity of exopolysaccharides such as carbohydrates from 0.256 ± 0.013 to 0.637 ± 0.014 and proteins from 0.124 ± 0.028 to 0.361 ± 0.016 which initiates firm accumulation on the polymer surface, and which leads the degradation of polyethylene by mineralization. This work provides a comprehensive result to accelerate the biodegradation of polyethylene at larger scales using different species and consortium of microalgae. The future study of enzymes involved in the biodegradation process will lead to effective and potential method of polymer waste disposal.